Variability of the conserved V3 loop tip motif in HIV-1 subtype B isolates collected from Brazilian and French patients - Tomasini-Grotto, Rejane-Maria [UNESP]; Montes, Brigitte; Triglia, Denise [UNESP]; Torres- Braconi, Carla; Aliano-Block, Juliana; Zanotto, Paolo M. de A.; Pardini, Maria Ines de Moura Campos [UNESP]; Segondy, Michel (Sociedade Brasileira de Microbiologia, 2010)
The diversity of the V3 loop tip motif sequences of HIV-1 subtype B was analyzed in patients from Botucatu (Brazil) and Montpellier (France). Overall, 37 tetrameric tip motifs were identified, 28 and 17 of them being recognized in Brazilian and French patients, respectively. The GPGR (P) motif was predominant in French but not in Brazilian patients (53.5% vs 31.0%), whereas the GWGR (W) motif was frequent in Brazilian patients (23.0%) and absent in French patients. Three tip motif groups were considered: P, W, and non-P non-W groups. The distribution of HIV-1 isolates into the three groups was significantly different between isolates from Botucatu and from Montpellier (P < 0.001). A higher proportion of CXCR4-using HIV-1 (X4 variants) was observed in the non-P non-W group as compared with the P group (37.5% vs 19.1%), and no X4 variant was identified in the W group (P < 0.001). The higher proportion of X4 variants in the non-P non-W group was essentially observed among the patients from Montpellier, who have been infected with HIV-1 for a longer period of time than those from Botucatu. Among patients from Montpellier, CD4+ cell counts were lower in patients belonging to the non-P non-W group than in those belonging to the P group (24 cells/µL vs 197 cells/µL; P = 0.005). Taken together, the results suggest that variability of the V3 loop tip motif may be related to HIV-1 coreceptor usage and to disease progression. However, as analyzed by a bioinformatic method, the substitution of the V3 loop tip motif of the subtype B consensus sequence with the different tip motifs identified in the present study was not sufficient to induce a change in HIV-1 coreceptor usage.
Keywords: HIV-1; V3 loop; Genetic diversity; Brazil; France